HUBUNGAN ANTARA PENGGUNAAN GAWAI DENGAN MINAT BELAJAR BAHASA INDONESIA SISWA SMKN 6 PANGKEP - Nurannisa Dwisahrah; Sulastriningsih Djumingin (Universitas Negeri Makassar, 2020)
The relationship between the use of gadgets and the students' interest in learning Indonesian at SMKN 6 Pangkep. This study aims to determine how much the relationship between device use and students' interest in learning Indonesian. Determination of the sample using the Total Sampling technique. Data collection was carried out using a questionnaire. Data analysis used Product Moment analysis with the help of the Statistical Package for Social Science (SPSS) data processing program. The results showed that there was a significant relationship between the intensity of the use of the device and the students' interest in learning Indonesian at SMK Negeri 6 Pangkep.